Relationship between outpatient antibiotic use and the prevalence of bacterial infections in Montenegro - Šahman-Zaimović, Majda M; Vukmirović, Saša; Tomić, Nataša; Stilinović, Nebojša; Horvat, Olga; Tomić, Ljiljana (Vojnosanitetski pregled, 2017)
Background/Aim. The overuse of antibiotics unnecessarily exposes patients to risk of side effects, encourages reconsultation for similar problems and enhances antimicrobial resistance. The use of antibiotics in the year 2011 in Montenegro was high (39.05 Defined Daily Dose – DDD/1,000 inhabitants/day), but it was not considered in relation to the frequency of bacterial diseases. The aim of our study was to determine the degree of conformance between the amount of outpatient antibiotic consumption and the reported prevalence of outpatient bacterial infections in the Republic of Montenegro. Methods. Data on the use of antibacterial drugs was obtained from the Agency for Medicines and Medical Devices of Montenegro for the year 2012. The amount of antibiotics was calculated using the Anatomic Therapeutic Chemical (ATC) DDD methodology. Data on the prevalence of outpatient infective disease was obtained from the Health Statistical Yearbook 2012 of Montenegro and it was expressed per 1,000 inhabitants. Results. A total of 30.34 DDD/1,000 inhabitants/day of antibiotics in outpatients were prescribed in Montenegro in 2012, with penicillins being most frequently prescribed. Amoxicillin and amoxicillin with clavulanic acid were the most frequently used antibiotics. The prevalence of outpatient bacterial infections was 6,745 cases or 10.87/1,000. The most frequent infections were respiratory tract infections. Less than 50% of the prescribed amount of antibiotics were prescribed in accordance with national guidelines on treatment of bacterial infections. Conclusion. Use of antibiotics in Montenegro in 2012 was more than double than necessary according to prevalence of bacterial infections and average duration of treatment. The structure of antibiotics was not in full compliance with the national good practice guidelines, but it was in accordance with data on bacterial antibiotic resistance in outpatient practice. It is necessary to initiate measures to rationalize the use of antibiotics both in terms of quantity and in terms of the structure of the most used antibiotics.